In Silico Study of the Potential of Moringa oleifera Secondary Metabolites as α-Glucosidase Inhibitors - Bumulo, Nuraini; Aman, La Ode; Kilo, Jafar La; La Kilo, Akram; Salimi, Yuszda K.; Arviani, Arviani (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
This study aims to evaluate the potential of Moringa oleifera secondary metabolites as inhibitors of the α-glucosidase enzyme using an in silico approach. The study employed molecular docking methods. The structure of the α-glucosidase enzyme was obtained from the Protein Data Bank (PDB ID: 3TOP), while the structures of Moringa oleifera secondary metabolites were sourced from the literature. Docking simulations were conducted using AutoDock Vina, and interaction results were analyzed using Discovery Studio. The analyzed parameters included binding affinity values and the interactions between ligands and active site residues of the enzyme. The results showed that several secondary metabolites of Moringa oleifera, such as lutein and 4-(α-L-rhamnopyranosyloxy)benzyl glucosinolate, exhibited strong binding affinity values: -10.93 kcal/mol for lutein and -10.27 kcal/mol for 4-(α-L-rhamnopyranosyloxy)benzyl glucosinolate. Benzyl glucosinolate enhanced the stability of the ligand-protein complex, demonstrating its potential as a more effective α-glucosidase inhibitor compared to acarbose, the currently used antidiabetic drug. Based on molecular docking analysis, the secondary metabolites of Moringa oleifera indicate great potential for further development as antidiabetic agents.